2016
DOI: 10.1167/iovs.15-18986
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis Predicts Large Optic Nerve Head Strains During Horizontal Eye Movements

Abstract: Our models predicted high ONH strains during eye movements, which were aggravated with stiffer optic nerve sheaths. Further studies are needed to explore links between ONH strains induced by eye movements and axonal loss in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
176
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(184 citation statements)
references
References 62 publications
8
176
0
Order By: Relevance
“…This is not biologically accurate as the LC has a thickness of approximately 270 lm. 58 Considering that the LC may exhibit highly heterogeneous stresses (induced by IOP, the retrolaminar pressure, or during eye movements 59 ), it would be logical to observe variations in LC hemodynamics and oxygen concentrations through the thickness of the LC, as predicted by Causin et al 20 LC thickness has also been shown to change with glaucoma progression, which may in turn compromise blood flow further in glaucoma subjects. 8 While using 'surface-like' LCs (as performed herein) should provide a first degree of understanding of LC hemodynamics, future improvements to our models should prioritize on incorporating LC thickness and interactions with LC stresses.…”
Section: Discussionmentioning
confidence: 97%
“…This is not biologically accurate as the LC has a thickness of approximately 270 lm. 58 Considering that the LC may exhibit highly heterogeneous stresses (induced by IOP, the retrolaminar pressure, or during eye movements 59 ), it would be logical to observe variations in LC hemodynamics and oxygen concentrations through the thickness of the LC, as predicted by Causin et al 20 LC thickness has also been shown to change with glaucoma progression, which may in turn compromise blood flow further in glaucoma subjects. 8 While using 'surface-like' LCs (as performed herein) should provide a first degree of understanding of LC hemodynamics, future improvements to our models should prioritize on incorporating LC thickness and interactions with LC stresses.…”
Section: Discussionmentioning
confidence: 97%
“…16 Briefly, the optic nerve, orbital fat, and eye globe were reconstructed from MRI images of a healthy subject. The ONH geometry, including the peripapillary sclera, scleral flange, prelaminar neural tissue, lamina cribrosa, postlaminar neural tissue, pia, and dura, was embedded within an ''idealized'' spherical corneoscleral shell.…”
Section: Geometry Of the Fe Modelmentioning
confidence: 99%
“…Detailed geometric parameters of these tissues can be found in the recent literature. 16 We further included the choroid and BM into the model to increase its biofidelity and to estimate stresses in the regions in which peripapillary zones typically develop. The thickness of the choroid and BM were 134 lm 19 and 5 lm, 20 respectively.…”
Section: Geometry Of the Fe Modelmentioning
confidence: 99%
See 2 more Smart Citations